2018
DOI: 10.1016/j.cell.2018.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Control of CNS Myelination by Oligodendrocyte Programmed Cell Death through the TFEB-PUMA Axis

Abstract: SUMMARY Nervous system function depends on proper myelination for insulation and critical trophic support for axons. Myelination is tightly regulated spatially and temporally, but how it is controlled molecularly remains largely unknown. Here, we identified key molecular mechanisms governing the regional and temporal specificity of central nervous system (CNS) myelination. We show that transcription factor EB (TFEB) is highly expressed by differentiating oligodendrocytes and that its loss causes precocious and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(155 citation statements)
references
References 50 publications
9
145
1
Order By: Relevance
“…iTBS could act directly on premyelinating oligodendrocytes to influence their survival, as the transcription factor EB can turn on expression of Bbc3 (Bcl binding component 3) and activate Bax‐Bak signaling to trigger apoptotic cell death (Sun et al, ). However, it is also possible that this effect is secondary to an increase in neuronal activity (Kougioumtzidou et al, ; Palser, Norman, Saffell, & Reynolds, ; Trapp et al, ; Xiao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…iTBS could act directly on premyelinating oligodendrocytes to influence their survival, as the transcription factor EB can turn on expression of Bbc3 (Bcl binding component 3) and activate Bax‐Bak signaling to trigger apoptotic cell death (Sun et al, ). However, it is also possible that this effect is secondary to an increase in neuronal activity (Kougioumtzidou et al, ; Palser, Norman, Saffell, & Reynolds, ; Trapp et al, ; Xiao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the activation of GABA A Rs in Cajal Retzius neurons, for which GABA is also depolarizing, causes their programmed cell death through dynamic changes of intracellular Cl − concentrations involving the Cl − transporter NKCC1 and p75NTR signaling (Blanquie, Liebmann, Hübner, Luhmann, & Sinning, ; Kolbaev, Luhmann, & Kilb, ). Programmed cell death is also an important mechanism of oligodendroglia to ensure OL lineage cell balance and region‐specific myelination (Kessaris et al, ; Sun et al, ). It would thus be interesting to test if a mechanism similar to that described for Cajal Retzius neurons, whether synaptic or extrasynaptic, promotes either the death or the survival of oligodendroglia.…”
Section: Gaba In Neuron–oligodendroglia Communicationmentioning
confidence: 99%
“…Markers for pre‐OLs are relatively less well characterized. A recent study reported that TFEB (transcription factor EB) is highly enriched in pre‐OLs and can be used as a pre‐OL marker . In addition, O4 has been also suggested as a pre‐OL marker, although there is also evidence showing that it is also expressed in mature‐OLs .…”
Section: Oligodendrocyte Physiologymentioning
confidence: 99%
“…A recent study reported that TFEB (transcription factor EB) is highly enriched in pre-OLs and can be used as a pre-OL marker. 48 In addition, O4 has been also suggested as a pre-OL marker, 40,44,49 although there is also evidence showing that it is also expressed in mature-OLs. 50,51 Mature-OLs form myelin sheaths and express a group of unique proteins, including MYRF (myelin regulatory factor), 52 MBP (myelin basic protein), 38,44,53 MOG (myelin oligodendrocyte glycoprotein), [54][55][56] PLP (proteolipid protein), 44,53,57 and MAG (myelin-associated glycoprotein).…”
Section: Opc Differentiationmentioning
confidence: 99%